2016
DOI: 10.1038/srep24599
|View full text |Cite
|
Sign up to set email alerts
|

Single-step cycle pulse operation of the label-free electrochemiluminescence immunosensor based on branched polypyrrole for carcinoembryonic antigen detection

Abstract: A novel label-free electrochemiluminescence (ECL) immunosensor based on luminol functional-Au NPs@polypyrrole has been developed for the detection of carcinoembryonic antigen (CEA). In this work, polypyrrole prepared by chemical polymerization provided a large surface area to load amounts of gold nanoparticles (Au NPs). Au NPs could not only attach abundant luminol for the enhancement of ECL signal, but also provide a friendly microenvironment for the immobilization of antibodies. Moreover, 1-butylpyridinium t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…Subsequently, the FT-IR spectrum was recorded as shown in Figure 1c, in which the typical peaks of 1552, 1317, 1187, and 917 cm −1 prove the successful preparation of PPy according to the literature. 42,43 These data proved that PPy NPs with excellent monodispersity in aqueous solution and with a diameter of about 70 nm were successfully prepared. This should be due to the fact that the complexation of Fe 3+ with the water-soluble PVA chain resulted in a slow polymerization of PPy, and during the polymerization, the water-soluble PVA provided sufficient steric stability for the nuclei of PPy NPs.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…Subsequently, the FT-IR spectrum was recorded as shown in Figure 1c, in which the typical peaks of 1552, 1317, 1187, and 917 cm −1 prove the successful preparation of PPy according to the literature. 42,43 These data proved that PPy NPs with excellent monodispersity in aqueous solution and with a diameter of about 70 nm were successfully prepared. This should be due to the fact that the complexation of Fe 3+ with the water-soluble PVA chain resulted in a slow polymerization of PPy, and during the polymerization, the water-soluble PVA provided sufficient steric stability for the nuclei of PPy NPs.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…The FTIR spectrum of PPy shows the typical peaks that can be attributed to the C−H in-plane deformation vibration at 1039 cm −1 and the ring-tensile mode of the Py ring at 1547 cm −1 . 32,33 These typical peaks from PPy are clearly shown in the FTIR spectrum of AFCP (1046 and 1555 cm −1 ). This further suggested that the PPy NPs have been successfully coated on the electrospun fibers.…”
Section: Fabrication Of Aligned Pcl-col-ppy Scaffolds Bymentioning
confidence: 94%
“…Zhu et al constructed a novel ECL immune-based biosensor using anti-CEA–luminol–AuNP@PPy ( Figure 11 A) [ 144 ]. The PPy nanostructure made it possible to enhance the conductivity of the biosensor and provided a high specific surface area for the combination with the AuNPs, thus enabling the attachment of abundant amounts of the ECL reagent (luminol) and promoting the immobilization of antibodies.…”
Section: Ppy-based Biosensors For Crc Biomarker Detectionmentioning
confidence: 99%